Transcending Organizational Compassion Paradoxes by Enacting Wise Compassion Courageously. (October 2020) - Simpson, Ace V.; Berti, Marco
While organizational compassion has attracted increased scholarly interest over the past two decades, inherent paradoxical tensions have been largely overlooked. Transcendence of oppositions is widely recognized as the most effective paradox response. To gain insight about the transcendence of the paradoxical tensions in organizational compassion, we turn to the cultural context of Bhutan, where for centuries compassion has been held as a central virtue informing governance and daily life. Our analysis contributes to the literature on organizational compassion and on organizational paradoxes by (a) theorizing the application of Bhutan's compassion transcendence strategies to the organizational context, (b) thereby engaging in cross-cultural analysis hereto overlooked in the organizational compassion literature, (c) highlighting paradoxes in compassion relations, and (d) providing a generalizable sociomaterial model for studying paradox transcendence.